IMPROVING ADHERENCE TO ISONIAZID PREVENTIVE THERAPY IN EASTLANDS, NAIROBI: IDENTIFYING CHALLENGES AND IMPLEMENTING STRATEGIES - Otieno, Michael Omondi (Ayden International Journal of Basic and Applied Sciences, 2024)
Tuberculosis (TB) remains a formidable global health challenge, particularly for individuals living with HIV (PLHIV). According to the World Health Organization (WHO), TB was ranked among the top ten causes of death for PLHIV in 2016, with a significant impact on global public health. This study sheds light on the alarming resurgence of TB, primarily affecting countries with high HIV prevalence. With over ten million reported TB cases worldwide, of which more than one million involve PLHIV, the need for effective prevention and management strategies is critical. Isoniazid Preventive Therapy (IPT) has emerged as a crucial intervention to mitigate the rising burden of TB, especially in high TB-burden areas. However, the uptake of IPT has been disappointingly low, with just one million newly enrolled PLHIV receiving IPT in 2015. Alarmingly, in 16 high TB burden countries, the coverage of IPT remains as low as 2%. Barriers such as medication costs, resource constraints in managing treatment completion, and supply chain issues pose significant challenges to IPT implementation. Additionally, the shifting of certain tasks related to patient management and medication dispensing presents an ongoing challenge that needs to be addressed to alleviate the burden on both patients and healthcare providers. Africa bears the brunt of the global HIV-positive TB cases, accounting for 74% of all such cases. Over the past two decades, 22 high burden countries (HBCs) have received international attention for their efforts to combat TB. The opportunistic nature of TB makes it a constant threat to individuals living with HIV, particularly during the early months of antiretroviral treatment (ART), whether in resourceconstrained or industrialized settings.